Pengaruh profesionalisme, gaya kepemimpinan, lingkungan kerja dan kecerdasan emosional terhadap kinerja pengelola keuangan pada Satuan Kerja Perangkat Daerah (SKPD) Kabupaten Indragiri Hilir - Zulfardiansyah NS; Vince Ratnawati; Yesi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research was to determine the effect of professionalism, leadership style, work environment and emotional intelligence on the performance of financial manager in SKPD regency Indragiri Hilir. The sample of this research amounted to 80 people , while the population of this research is a financial manager in the enviroment SKPD regency Indragiri Hilir. The data was collected using a questionnaire which was then analyzed by multiple regression linier. The results show that the professionalism, leadership style, and emotional intelligence have a significant effect on the performance of financial manager in SKPD regency Indragiri Hilir, whereas no significant effect on the work environment. Donations effect of independent variables on the dependent variable is equal to 65.9 % .Keywords : financial manager Performance , Professionalism , Leadership Style , Emotional Intelligence and Work Environment